Pollen flow of Theobroma cacao and its relationship with climatic factors in the central zone of the Ecuadorian Littoral (Bioagro, 2020)
Ecuador is known worldwide as a major producer of Theobroma cacao “fine aroma”, although yields per hectare are in general low. It is one of the most studied tropical species, but there is little scientific information to identify the elements that cause this low productivity which could be related to an inefficient pollen flow. The aim of this research was to quantify pollen flow in clones of Theobroma cacao and to assess which climatic factors condition the arrival of pollen to stigmas. The study was carried out in Quevedo, Los Ríos Province, in the Ecuadorian Littoral with a tropical climate. Flowers of different clones were collected for six months. At the beginning of the rainy season (February) the highest pollen flow was observed, with differences between clones varying from 9 to 25 grains per flower, being the clones of Trinitarian origin where the highest arrival of pollen was found, while in the National type clones the lowest reception of pollen grains per flower was recorded. Only 12% of flowers analyzed received more than 25 grains per flower. This flow of pollen is insufficient to withstand pod formation in the cacao trees, which is reflected in the low percentage of tied fruits (effective pollination). The quantified pollen on stigmas is partially determined by the maximum temperature (r=0.46), with minor effects of precipitation (r=0.33), wind speed (r=0.29) and relative humidity (r = 0.27).
Keywords: Effective pollination; Malvaceae; reproduction; viability